Are You Zoomed In? Considerations for Successfully Navigating Virtual Professional Development. Issue 1 (25th November 2020) - Brooks, Collin; Fan, Xiaoping; McMullen, Jaimie M.
Abstract : This article will provide readers with some practically relevant tips for successfully engaging in virtual professional development, including how to prepare for the experience, how to engage during the event, and what to do after the professional development session is over.